Temperature and nutrients control the presence and distribution of long-chain diols in Swiss lakes - Lattaud, Julie; Martin, Céline; Lloren, Ronald; Zborovsky, Beata; Dubois, Nathalie (Frontiers in Earth Science, 2024)
Long-chain diols are biomarkers commonly used in the marine realm to reconstruct several environmental parameters such as sea surface temperature and salinity. However, they are also produced in lacustrine and slow-flowing river environments, a characteristic that has proved to be useful to trace past riverine inputs in coastal sedimentary records. So far, their use in lacustrine settings is sparse as their controls are not well-known. Previous studies in two lakes have shown that long-chain diol distribution is linked to changes in temperature (in a small Spanish alpine lake), but also to water column stratification (in a large deep Swiss lake). To understand the controls on i) the presence of longchain diols in lakes, and ii) the distribution of long-chain diol isomers, surface sediments from 52 Swiss lakes were studied. Long-chain diols are present in 57% of the lakes, and machine learning (i.e., random forest model) showed that their presence is mainly controlled by mean annual air temperature, sodium and potassium concentrations and area of the lakes. Long-chain diol isomer relative distribution seems to react to temperature, nutrient (here nitrate) and oxygen concentrations in the lakes. This new insight was tested on a short sedimentary core from Lake Zurich, and compared with other biomarker proxies (based on branched and isoprenoid glycerol dialkyl glycerol tetraethers), as well as with historical record of nutrient contents and temperature. Variations in the long-chain diol index (LDI) mirror measured temperature, but also reacted to changes in nutrients and oxygenation in the lake. This study highlights the potential of long-chain diols as a proxy to trace both nutrients and temperature in lakes, potentially on geological timescales.